Infection of prepubertal heifer calves as a natural host model for Tritrichomonas foetus - Martin, Katy A.; Reece, Sara; Jesudoss Chelladurai, Jeba R. J.; Harm, Tyler A.; Smith, Jodi D.; Blake, Courtney N.; Jones, Douglas E.; Kovach, Kris; McMahan, Krysta; Moscoso, Erica; Ostrander, Morgan; Brewer, Matthew T. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionTritrichomonas foetus is a sexually transmitted flagellate that causes economic loss in the cattle industry throughout the world. In the United States, there are no approved treatments for the parasite. Owing to its transmission strategy, T. foetus typically infects cattle of breeding age. However, in vivo studies of treatment, diagnostic strategies, and vaccination are severely hampered by the maintenance and cost of maintaining adult cattle in research settings. In this study, we investigated the utility of infecting pre-pubescent heifer calves with T. foetus.MethodsFour independent cohorts of cross-bred prepubertal heifer calves were vaginally inoculated with T. foetus trophozoites previously derived from a naturally-infected bull. Infections were assessed by culture, PCR, DNA sequencing, histopathology, gross pathology, and lesion scoring. In addition, reproductive tract tissue was assessed for the presence of galectin-1, a putative receptor for T. foetus trophozoite adhesion.ResultsOur experiments revealed that despite being in anestrus, heifer calves were amenable to infection with trophozoites for as long as 42 days post-infection as determined by PCR and culture of the organism. Histopathology revealed inflammation throughout the reproductive tract of infected calves. Infection resulted in endometritis with lymphoplasmacytic infiltration and demonstrated that trophozoites could pass through the cervix even during anestrus in prepubescent heifers. In addition, immunohistochemistry of the vagina, cervix, and uterus demonstrated robust expression of galectin-1.ConclusionOur experiments demonstrated that prepubertal heifer calves are a suitable natural host model for bovine trichomonosis. This is a significant breakthrough in the field and also has potential for advancing the human trichomoniasis research agenda.